KEPEMIMPINAN VISIONER KEPALA MADRASAH MENUJU MADRASAH UNGGULAN STUDI KASUS DI MTSN 3 KEDIRI - A'yunin, Fitri Qurrota; Priyono, Ali (JoEMS (Journal of Education and Management Studies), 2021)
This study is aimed to describe the leadership role of the head of the madrasah and the achievement of a madrasah vision in becoming an excellent madrasah at MTsN 3 Kediri. The implementation of the vision formed by the madrasah principal together with the madrasah community was identified by analyzing primary data and secondary data at MTsN 3 Kediri. This study used a qualitative descriptive design. The data that was analyzed is data from the main source of this study, such as the head of the madrasah, besides the data analyzed is data in the form of writing, such as a brief history of MTsN 3 Kediri, and other documents related to the research. The analyzed data were a written data, such as a brief history of MTsN 3 Kediri, and other documents related to research. The results were analyzed using the Presistant technique (observation persistence) and Triangulation (combining various data collection techniques). The results of the study state that the visionary leadership of the Madrasah Principal towards the Excellent Madrasah at MTsN 3 Kediri is in accordance with the theory of Burt Nanus with a description of the formulation of a vision, the form of implementation / strategy of the principal, which is able to guarantee the realization of a superior madrasah.